Exploring EFL Students’ Perceptual Dimensions of SAMR Model Integration in Basic Writing: Beliefs, Values, Motives, Experiences, and Expectations - La Ode Nggawu; Nurindah; Anugrah Puspita Ayu Muhammad; Waode Ade Sarasmita Uke; Nurul Atma; Wahyudin Madil; Husniatul Amalia (JTP - Jurnal Teknologi Pendidikan, 2026)
The purpose of the present study is to examine university students’ perceptions of SAMR-based Basic Writing instruction, focusing on five main dimensions: beliefs, values, motive, experiences, and expectations. Through a quantitative descriptive research design, data were collected from the 40 undergraduate students of Basic Writing class through a Likert-scaled questionnaire administered after SAMR-informed lessons. Descriptive statistical analyses in the SPSS resulted in relatively high means of belief, value, motive and expectation (M = 3.23–3.69), which indicates strong cognitive acceptance to SAMR and positive perceptions with regards to its instruction utility. Negative-worded experience items showed low scores (M = 1.97–2.17), which suggests that students usually did not reject technical disturbance or problems. These findings support prior research on how SAMR might enhance language learning and digital competence through clarifying writing steps, motivating learners, and reducing technostress. Some practical suggestions are to improve the digital infrastructure of institutions, boost lecturer training in TPACK-SAMR, add ethical generative AI rules, and create scaffolded assignments that fit students' level of technological preparation. This study demonstrates that students possess favorable perceptions of SAMR-based Basic Writing training, evidenced by elevated levels of beliefs, values, motives, and expectations. The findings indicate that the SAMR model offers a viable pedagogical framework for enhancing academic writing in higher education; nevertheless, its efficacy is contingent upon instructor expertise and contextual assistance. Subsequent study ought to utilize mixed-methods or experimental designs and incorporate performance-based writing assessments to investigate the tangible effects of SAMR on writing quality.